Patient safety issues in rehabilitation for person with locomotor disabilities: a review - Deka, Kuldeep; Gogoi, Pranjal (International Journal of Research in Medical Sciences, 2019)
Since the publication of the Institute of medicine report, To Err Is Human: Building a safer health system, notes that errors in health care are a significant cause of death and injury and the emphasis on patient safety has steadily increased. The rehabilitation professionals engaged for the management of patient with locomotor disabilities should incorporate elements of patient safety into their practices and also to stimulate research associated with prevalence of analysis of error/harm which occurs during the rehabilitation phase and also to develop and validate certain specific measuring tools and instruments for patient safety issues.